Impact of Primary Tracheoesophageal Puncture on Outcomes after Total Laryngectomy. (January 2018) - Panwar, Aru; Militsakh, Oleg; Lindau, Robert; Coughlin, Andrew; Sayles, Harlan; Rieke, Katherine R.; Lydiatt, William; Lydiatt, Daniel; Smith, Russell
Objectives: To identify differences in postoperative wound complications associated with a primary tracheoesophageal puncture (TEP) at the time of laryngectomy versus no TEP. Study Design: Retrospective review of large national data set. Setting: Academic and nonacademic health care facilities in United States, contributing de-identified, risk-adjusted clinical data to the American College of Surgeons National Surgical Quality Improvement Program. Subjects and Methods: The National Surgical Quality Improvement Program data set for years 2006 to 2012 identified 430 patients who underwent total laryngectomy with or without a primary TEP. Patients who underwent a TEP at the time of laryngectomy (n = 68) were compared with patients who underwent laryngectomy without a TEP (n = 362). Postoperative wound complications and secondary outcomes, including medical complications and length of hospitalization, were compared between the groups. Results: The incidence of "superficial" and "deep or organ space" surgical site infection, medical complications, return to the operating room, and length of hospitalization were similar between the groups. Patients in the TEP group had a higher overall wound complication rate (relative risk, 2.02; 95% CI = 1.06-3.84; attributable risk, 8.17%; number needed to harm, 12). Conclusions: Performance of a primary TEP concurrent to total laryngectomy contributed to a small increase in attributable risk for overall wound complications but did not add substantial risk for "superficial" or "deep or organ space" surgical site infection, medical complications, or increased burden for resource utilization. These data may help inform patient choice and physician recommendations for primary alaryngeal speech rehabilitation.